2019
DOI: 10.1364/optica.6.001185
|View full text |Cite
|
Sign up to set email alerts
|

Flexible lensless endoscope with a conformationally invariant multi-core fiber

Abstract: The lensless endoscope represents the ultimate limit in miniaturization of imaging tools: an image can be transmitted through a (multi-mode or multi-core) fiber by numerical or physical inversion of the fiber's premeasured transmission matrix. However, the transmission matrix changes completely with only minute conformational changes of the fiber, which has so far limited lensless endoscopes to fibers that must be kept static. In this letter we report for the first time a lensless endoscope which is exempt fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…These results are congruous with the earlier observations stated in Ref. [59], demonstrating that BPM-Matlab models twisted fibers correctly. Fig.…”
Section: Multicore Fiber Propagation With Distal End Focusingsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are congruous with the earlier observations stated in Ref. [59], demonstrating that BPM-Matlab models twisted fibers correctly. Fig.…”
Section: Multicore Fiber Propagation With Distal End Focusingsupporting
confidence: 90%
“…However, the aperiodicity of patterns such as the Fermat's golden spiral core pattern [58] and pseudo-random or random patterns [54] have all been shown to reduce the side-lobes. Recent theoretical and experimental studies have shown that a conformationally invariant (bending resilient) MCF can be fabricated with twisted cores, thereby providing promising fibers for lensless endoscopes [59].…”
Section: Multicore Fiber Propagation With Distal End Focusingmentioning
confidence: 99%
See 1 more Smart Citation
“…For leached fiber bundles that do not have a shared clad for all cores, such as the ones used in our experiments, fiber bending may cause strong decorrelation of the wavefront, which will require faster optimization. Recently introduced MCF designs feature significantly reduced bend sensitivity ( 41 )and are especially attractive for applying our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative, speckle based incoherent imaging approaches [11,12,13,14], suffer from very low contrast of the acquired images. MCFs with bend-insensitive intercore phase relations have been fabricated [28]. However, these rely on a relatively small number of single-mode cores, suffering from low collection-efficiency and fill-factor.…”
Section: Main Text Introductionmentioning
confidence: 99%